2006
DOI: 10.1124/jpet.105.099648
|View full text |Cite
|
Sign up to set email alerts
|

Differential in Vivo Sensitivity to Inhibition of P-glycoprotein Located in Lymphocytes, Testes, and the Blood-Brain Barrier

Abstract: A major functional component of the blood-brain barrier is P-glycoprotein. In principle, inhibition of this efflux transporter would permit greater distribution of its substrates into the brain and increased central effects. Tariquidar and elacridar, potent and selective P-glycoprotein inhibitors, were investigated in this regard using the opioid loperamide as an in vivo probe in mice. Pretreatment with both inhibitors converted intravenous loperamide from a drug without central effects to one producing antino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
3
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 29 publications
(36 reference statements)
8
75
3
1
Order By: Relevance
“…TQD inhibited P-gp-mediated efflux of VPM across the BBB with an apparent half-maximum effective dose (ED 50 ) of 6.6 mg/kg (95% confidence interval: 4.9-8.2 mg/kg) which was in good agreement with previous data reported in mice for another P-gp substrate (loperamide, ED 50 : 5.7 mg/kg) [1]. Brain-to-plasma radioactivity ratios after 0 and 15 mg/kg of TQD were 0.23 and 3.15, respectively.…”
Section: Resultssupporting
confidence: 81%
“…TQD inhibited P-gp-mediated efflux of VPM across the BBB with an apparent half-maximum effective dose (ED 50 ) of 6.6 mg/kg (95% confidence interval: 4.9-8.2 mg/kg) which was in good agreement with previous data reported in mice for another P-gp substrate (loperamide, ED 50 : 5.7 mg/kg) [1]. Brain-to-plasma radioactivity ratios after 0 and 15 mg/kg of TQD were 0.23 and 3.15, respectively.…”
Section: Resultssupporting
confidence: 81%
“…The efficacy of drug transport by efflux transporters in a tissue depends on a number of factors, such as the nature and physical state of the surrounding lipids, interactions with other tissue-specific proteins, and tissue-specific regulation of the transporters (Löscher and Potschka, 2005a). Furthermore, it has been demonstrated recently in in vitro assays, including LLC-MDR1 cells and a mouse in vivo model, that Pgp in the BBB differs strikingly in its sensitivity to Pgp inhibitors from Pgp in other tissues (Choo et al, 2006). Thus, despite the negative in vitro results with VPA in kidney cell lines, we decided to examine the in vivo role of Pgp and MRPs in efflux of VPA from the brain.…”
Section: Valproate and Efflux Transporters 339mentioning
confidence: 99%
“…Choo et al (2006) found that the tariquidar dose in mice needed to increase the tissue penetration of […”
Section: Discussionmentioning
confidence: 99%
“…We expect k 1 to be roughly cell-and tissue-independent because it depends mostly on lipid lateral diffusion in the inner plasma membrane, although this has not yet been proven. In contrast, the value of the membrane concentration of efflux active P-gp can be changed in the simulations, as this parameter can differ between cultured cells (Polli et al, 2001;Tang et al, 2002) and between tissues (Choo et al, 2006;Kurnik et al, 2008).…”
Section: ϫ8mentioning
confidence: 99%